Multi-modal vibration energy harvesting using the piezoelectric effect - Wu, Hao (2016)
Over the past decade, the use of remote wireless sensing electronics has grown steadily. One main concern for the development of these kinds of devices is the power supply module. Rather than using the traditional batteries which require periodic maintenance as well as produce chemical waste, harvesting energy from the ambient environment provides a promising solution for implementing self-powered systems. Many kinds of energy sources existing in the environment can be used for energy harvesting, such as solar, wind, thermal gradient, and vibration. Among them, vibration is the most ubiquitous energy source that can be found everywhere in our daily life. There are various mechanisms to convert vibration energy into electrical energy, such as electromagnetic, electrostatic and piezoelectric transduction. Due to the property of high power density and ease of application, vibration energy harvesting using piezoelectric materials has attracted intense research interest in recent years.